2018
DOI: 10.28976/1984-2686rbpec201818169
|View full text |Cite
|
Sign up to set email alerts
|

Questionamentos em Aulas de Química: Um Estudo Comparativo da Prática Pedagógica em Diferentes Contextos Sociais

Abstract: Este trabalho apresenta e discute os resultados de uma pesquisa sobre o discurso em salas de aula de Química e que teve como objeto os questionamentos do professor e dos estudantes. Baseada no conceito de enquadramento oriundo da teoria sobre o discurso pedagógico de Basil Bernstein e nos tipos de iniciação de Hugh Mehan, a pesquisa teve como objetivo estudar a influência dos contextos sociais sobre a prática pedagógica de professores de Química e sua manifestação sobre seus questionamentos em sala de aula. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…This case indicated that the sequence of questions -even if conceived by researchers of the field as low demanding regarding the structure of the answers and their explanatory capacity (Lobato & Quadros, 2018;Paula & Lima;2010;Silva et al, 2018) -can promote reflections that help restructuring thoughts, especially when it displays the contradiction and the complexity of choices.…”
Section: Figure 1 Transcription Of the First Part Of The Interaction Between The Museum Educator And The Students In The Chemistry Sectiomentioning
confidence: 99%
“…This case indicated that the sequence of questions -even if conceived by researchers of the field as low demanding regarding the structure of the answers and their explanatory capacity (Lobato & Quadros, 2018;Paula & Lima;2010;Silva et al, 2018) -can promote reflections that help restructuring thoughts, especially when it displays the contradiction and the complexity of choices.…”
Section: Figure 1 Transcription Of the First Part Of The Interaction Between The Museum Educator And The Students In The Chemistry Sectiomentioning
confidence: 99%
“…Esse caso indicou que o encadeamento de perguntas de escolha -ainda que entendidas por pesquisadores da área como de baixa exigência quanto à estruturação da resposta e de pouca capacidade explicativa (Lobato & Quadros, 2018;Paula & Lima;2010;Silva et al, 2018) -pode promover reflexões que contribuem para reelaborar o pensamento, especialmente quando evidencia a contradição e a complexidade da escolha.…”
Section: As Interações Entre As Educadoras E Os Estudantesunclassified
“…The dialogues between teacher and students refer to a joint discussion in solving the math assignment. This means the material's text suggests the existence of an open communication between the subjects (weakened framework), by enabling students to participate in the discussion, in the dynamics of being questioned about the information present in the mathematical assignment, which can contribute to better use of students, even if this communication can configure an answer from the teacher in the most direct way, making few situations that prolong the dialogue impossible, in a way (SILVA; SOUZA; SANTOS, 2018;FERREIRA, 2019). According to Magalhães, Mortimer and Silva (2016), the engagement of students in situations of dialogue initiated by the questions is essential for the establishment of dialogues.…”
Section: D) the Criteria For Evaluating Pedagogical Practicementioning
confidence: 99%